Copper-Catalyzed Methylthiolation of Aryl Iodides and Bromides with Dimethyl Disulfide in Water - Wang, Ying-yu; Wu, Xiang-mei; Yang, Ming-hua (Synlett, 2020)
An efficient route to aryl methyl sulfides through the copper-catalyzed coupling reaction of aryl iodides or bromides with dimethyl disulfide in water is described. Electron-donating and electron-withdrawing functional groups in the substrates were tolerated, and the corresponding products were obtained in moderate to good yields.
Keywords: methylthiolation; aryl halides; dimethyl disulfide; aryl methyl sulfides; copper catalysis